Whole‐cell biocatalytic and de novo production of alkanes from free fatty acids in Saccharomyces cerevisiae. Issue 1 (19th January 2016) - Foo, Jee Loon; Susanto, Adelia Vicanatalita; Keasling, Jay D.; Leong, Susanna Su Jan; Chang, Matthew Wook
ABSTRACT: Rapid global industrialization in the past decades has led to extensive utilization of fossil fuels, which resulted in pressing environmental problems due to excessive carbon emission. This prompted increasing interest in developing advanced biofuels with higher energy density to substitute fossil fuels and bio‐alkane has gained attention as an ideal drop‐in fuel candidate. Production of alkanes in bacteria has been widely studied but studies on the utilization of the robust yeast host, Saccharomyces cerevisiae, for alkane biosynthesis have been lacking. In this proof‐of‐principle study, we present the unprecedented engineering of S. cerevisiae for conversion of free fatty acids to alkanes. A fatty acid α‐dioxygenase from Oryza sativa (rice) was expressed in S. cerevisiae to transform C12–18 free fatty acids to C11–17 aldehydes. Co‐expression of a cyanobacterial aldehyde deformylating oxygenase converted the aldehydes to the desired alkanes. We demonstrated the versatility of the pathway by performing whole‐cell biocatalytic conversion of exogenous free fatty acid feedstocks into alkanes as well as introducing the pathway into a free fatty acid overproducer for de novo production of alkanes from simple sugar. The results from this work are anticipated to advance the development of yeast hosts for alkane production. Biotechnol. Bioeng. 2017;114: 232–237. © 2016 The Authors. Biotechnology and Bioengineering Published by Wiley Periodicals, Inc. Abstract : The robust industrial yeast production host Saccharomyces cerevisiae has been under‐explored for the biosynthesis of alkanes, which are attractive biofuel candidates. In this proof‐of‐principle study, the authors presented the first report on alkane biosynthesis from free fatty acid precursors in S. cerevisiae via aldehyde intermediates. The versatile synthetic metabolic pathway devised was applied for both whole‐cell biocatalytic transformation of free fatty acid feedstock and de novo conversion of simple sugars to aldehydes and alkanes.